FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT DAN PERILAKU PENGGUNAAN SISTEM PEMBAYARAN DIGITAL: SEBUAH STUDI LITERATUR - Atika Jauharia Hatta; Nadia Fordia Rahmawati (AKUNTANSI DEWANTARA, 2025)
The use of information technology (IT) has become essential in modern society, facilitating digital transactions and promoting a cashless society that offers efficiency and convenience for users. Analyze the factors influencing customer intention and behavior toward digital payments..This study reviews 33 previous studies on factors affecting customer intention and behavior toward digital payments, and summarizing the results. The reviewed articles include publications from both within and outside Indonesia. Domestic articles indexed in Sinta and international articles indexed in Scopus and/or Google Scholar were selected. The analysis shows that performance expectancy, effort expectancy, social influence, facilitating conditions, perceived ease of use and perceived usefulness, are the main factors influencing the intention and behavior toward digital payment systems. These findings provide crucial insights for developing strategies to enhance digital payment adoption, including improving infrastructure, educating the public, and developing products that meet user expectation. Adding complexity to previous research by enriching the theoretical understanding of the factors that can influence consumer intentions and behaviors in using digital payment.